2012
DOI: 10.1007/s12594-012-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Lower Jurassic Sandstones of Shemshak Formation, Kerman Basin, Central Iran: Provenance, Source Weathering and Tectonic Setting

Abstract: Lower Jurassic sandstones of Shemshak Formation of Kerman basin, central Iran were analyzed for major and select trace elements to infer their provenance, palaeoweathering of source rocks and tectonic setting. Average modal framework components (Qt: F: L= 67.25: 2.41: 30.48) and chemical composition of the sandstones classify them as litharenites. The sandstones are quartz-rich (∼ 67% quartz; 75.34 wt.% SiO2) and derived from a recycled orogen composed of quartzose sedimentary rocks. Average CIA, PIA and CIW v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The siliciclastic Shemshak Group (Up per Tri as sic-Mid dle Ju rassic) is one of the most ex ten sive lithostratigraphic units of the Iran Plate, wide spread across the north ern Alborz and East Cen tral Iran of the Ira nian plate (Tabas and North of Kerman; Fürsich et al, 2009). Nu mer ous stud ies have doc u mented lithostratigraphic, sedimentological and palaeontological aspects of the Shem shak Group (e.g., Seyed-Emami et al, 2006;Fürsich et al, 2009;Shekarifard et al, 2009;Zanchi et al, 2009;Moosavirad et al, 2011Moosavirad et al, , 2012Abbassi and Madanipour, 2014;Salehi et al, 2017). These stud ies have shown that the Shemshak Group is com posed largely of siliciclastic rock, lo cally reach ing up to 4000 m in thick ness.…”
Section: Introductionmentioning
confidence: 99%
“…The siliciclastic Shemshak Group (Up per Tri as sic-Mid dle Ju rassic) is one of the most ex ten sive lithostratigraphic units of the Iran Plate, wide spread across the north ern Alborz and East Cen tral Iran of the Ira nian plate (Tabas and North of Kerman; Fürsich et al, 2009). Nu mer ous stud ies have doc u mented lithostratigraphic, sedimentological and palaeontological aspects of the Shem shak Group (e.g., Seyed-Emami et al, 2006;Fürsich et al, 2009;Shekarifard et al, 2009;Zanchi et al, 2009;Moosavirad et al, 2011Moosavirad et al, , 2012Abbassi and Madanipour, 2014;Salehi et al, 2017). These stud ies have shown that the Shemshak Group is com posed largely of siliciclastic rock, lo cally reach ing up to 4000 m in thick ness.…”
Section: Introductionmentioning
confidence: 99%
“…The geochemical studies had long been used for provenance studies of clastic sediments (Yan et al, 2002;Moosavirad et al, 2012). Al 2 O 3 /TiO 2 ratios in the sedimentary rocks are considered as an important tool to find out the types of source rocks (Garcia et al, 1994;Hayashi et al, 1997).…”
Section: Provenancementioning
confidence: 99%
“…Geochemical studies on clastic rocks had long been used to unravel the provenance signatures (Madhavaraju and Ramasamy, 2002;Yan et al, 2002;Armstrong-Altrin et al, 2004;Nagarajan et al, 2007a,b;Paikaray et al, 2008;Moosavirad et al, 2012;Madhavaraju, 2015;Ramachandran et al, 2016). The rare earth elements and certain trace elements (Y, Th, Zr, Hf, Nb, and Sc) are most suited for discriminations of provenance and tectonic setting because of their relatively low mobility during sedimentary processes and their short residence times in seawater (Taylor and Mclennan, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The geochemistry of clastic sedimentary rocks is used as an effective tool in the study of source area composition (Cullers, 2000(Cullers, , 2002Osae et al, 2006;Armstrong-Altrin, 2009;Saha et al, 2010), intensity of chemical weathering in the source region (Selvaraj and Chen, 2006;Roy et al, 2008;Gallala et al, 2009;Gupta et al, 2012;Raza et al, 2012), paleoclimatic conditions (Nesbitt and Young, 1982;Bhatia, 1983;Taylor and McLennan, 1985;Absar et al, 2009;Raza et al, 2010), provenance (Cullers, 2000(Cullers, , 2002Armstrong-Altrin, 2009;Bakkiaraj et al, 2010) and tectonic setting of the sedimentary basins (Cullers, 2000;Armstrong-Altrin and Verma, 2005;Joo et al, 2005;Sabaou et al, 2009;Fatima and Khan, 2012). The geochemical composition of clastic sediments is a complex function and depends on other factors such as physical sorting, diagenesis, source material and relief (Nagarajan et al, 2007a(Nagarajan et al, , 2007bArmstrong-Altrin et al, 2004Moosavirad et al, 2012). Likewise, geochemical parameters have been used by various authors to understand the paleo-oxygenation conditions of ancient sediments (Calvert and Pedersen, 1993;Jones and manning, 1994;Nath et al, 1997;Madhavaraju and Ramasamy, 1999;Cullers, 2002;Armstrong-Altrin et al, 2003;Dobrzinski et ...…”
Section: Introductionmentioning
confidence: 99%